2009
DOI: 10.2460/ajvr.70.4.527
|View full text |Cite
|
Sign up to set email alerts
|

Effect of parenteral administration of ivermectin and erythromycin on abomasal emptying rate in suckling calves

Abstract: OBJECTIVE-To evaluate the effect of parenteral administration of ivermectin and erythromycin on abomasal emptying rate in suckling calves. ANIMALS-6 male Holstein-Friesian calves < 15 days old. PROCEDURES-In a crossover study, calves were administered each of 3 treatments (control treatment, 2 mL of saline [0.9% NaCl] solution, IM; erythromycin, 8.8 mg/kg, IM; and ivermectin, 200 microg/kg, IV). Thirty minutes later, calves were bottle-fed 2 L of fresh cow's milk containing acetaminophen (50 mg/kg). Blood samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 20 publications
(29 reference statements)
2
17
0
Order By: Relevance
“…In the present study, as in other studies, 18,23,24,44 T max obtained from a pharmacokinetic model (equivalent to T maxmodel in the present study) provided the most accurate estimation of emptying rate. A previous study 8 explored the suitability of these parameters to estimate the abomasal emptying rate in calves by comparing values of these parameters with values obtained via scintigraphy.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, as in other studies, 18,23,24,44 T max obtained from a pharmacokinetic model (equivalent to T maxmodel in the present study) provided the most accurate estimation of emptying rate. A previous study 8 explored the suitability of these parameters to estimate the abomasal emptying rate in calves by comparing values of these parameters with values obtained via scintigraphy.…”
Section: Discussionsupporting
confidence: 82%
“…An unexpected finding of this study was the minimal effect that oral erythromycin lactobionate (20 mg/kg BW) had on indices of abomasal emptying rate and the total IgG and total protein‐time relationships. Previous studies have consistently demonstrated that IM administration of erythromycin (8.8–10 mg/kg BW) produced a marked prokinetic effect in milk‐fed calves and adult cattle 5, 14, 15, 16, 17, 18, 19. Erythromycin base is not absorbed in preruminant calves when administered orally at 10 mg/kg; this result has been attributed to acid destruction of erythromycin in the abomasum 37.…”
Section: Discussionmentioning
confidence: 99%
“…We were, therefore, interested in determining the effect of potential nonantimicrobial prokinetic agents, such as cisapride and bethanechol, on abomasal emptying rate and AEA in neonatal calves, and in comparing their prokinetic effects to a positive control (erythromycin) and a negative control (0.9% NaCl solution). Erythromycin was selected as the positive control because it is known to be a strong prokinetic agent in milk‐fed calves and adult cattle 14, 15, 16, 17, 18, 19. Cisapride was investigated because it increases the rate of gastrointestinal motility in the cat, dog, and horse 20.…”
mentioning
confidence: 99%
“…, 2008), and calves (Wittek & Constable, 2005; Nouri & Constable, 2007; Nouri et al. , 2008; Afshari et al. , 2009).…”
Section: Pharmacokinetic Values (Mean ± Sd) Of Acetaminophen In Diffmentioning
confidence: 99%